Stapler vs suture closure of pancreatic remnant after distal pancreatectomy: a meta-analysis - Zhou, Wei; Lv, Ran; Wang, Xianfa; Mou, Yiping; Cai, Xiujun; Herr, Ingrid (The American journal of surgery, 2010)
Background - Suture closure and stapler closure of the pancreatic remnant after distal pancreatectomy are the techniques used most often. The ideal choice remains a matter of debate. - Methods - Five bibliographic databases covering 1970 to July 2009 were searched. - Results - Sixteen articles met the inclusion criteria. Stapler closure was performed in 671 patients, while suture closure was conducted in 1,615 patients. The pancreatic fistula rate ranged from 0% to 40.0% for stapler closure of the pancreatic stump and from 9.3% to 45.7% for the suture closure technique. There were no significant difference between the stapler and suture closure groups with respect to the pancreatic fistula formation rate (22.1% vs 31.2%; odds ratio, .85; 95% confidence interval, .66-1.08), although there was a trend toward favoring stapler closure. In 4 studies including 437 patients, stapler closure was associated with a trend (not statistically significant) toward a reduction in intra-abdominal abscess (odds ratio, .53; 95% confidence interval, .24-1.15). - Conclusions - No significant differences occur between suture and stapler closure with respect to the pancreatic fistula or intra-abdominal abscess after distal pancreatectomy, though there is a trend favoring stapler closure.
Gesehen am 09.02.2024